Chemical characterization and antioxidant activity of Eryngium campestre L., Apiaceae from Kosovo - Flurim Nebija; Gjoshe Stefkov; Marija Karapandzova; Trajche Stafilov; Tatjana Kadifkova Panovska; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2009)
This study is outlined to define the chemical composition and in vitro antioxidant activity of the extracts of aerial part and root of Eryngium campestre L. (Apiaceae) from Kosovo. Analysis of the chemical composition include determination of total ash, ash insoluble in hydrochloric acid, loss on drying and the content of water extract, as well as determination of flavonoids in aerial part and hemolytic activity of the root. The mineral composition (Zn, Fe, Cu, Mn, Ni, K, Co, Pb, Cd and Cr) in aerial parts and root has been studied using atomic absorption spectroscopy (AAS and ETAAS). Different part of E. campestre accumulate different amounts of investigated minerals. Antioxidant activity was determined by four various testing systems: DPPH assay, inhibition of production of hydroxyl radical, β-carotenebleaching assay, and inhibition of lipid peroxidation (TBA test). In DPPH system, ethanol extract of root of E. campestre exhibited higher radical-scavenging activity (IC50 = 0.72 mg ml-1) compared to the extract of the aerial part (IC50 = 1.14 mg ml-1). On the other hand, aerial part ethanol extract has exhibited stronger inhibition capacity on the production of hydroxyl radical in deoxyribose system than the root extract (50% and 45%, respectively). However, both ethanol extracts of E. campestre exhibited low antioxidant activity in β-carotenebleaching assay as well as, low capacity for inhibition of spontaneous lipid peroxidation in rat liver homogenate.